2007
DOI: 10.1063/1.2431860
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic chip-based synthesis of alginate microspheres for encapsulation of immortalized human cells

Abstract: Cellular transplantation is a promising technology with great clinical potential in regenerative medicine and disease management. However, effective control over patient immunological response is essential. The encapsulation of cells within hydrogel microspheres is an increasingly prevalent method for the protection of cellular grafts from immune rejection. Microfluidic "chip" reactors present elegant solutions to several capsule generation issues, including the requirement for intercapsule uniformity, high re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 19 publications
1
70
0
1
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14] Non-spherical microgel, such as rod-like, wedge-like, and disk-like microgels, can also be prepared via well-designed microfluidic channels or mask-photopolymerization. [15][16][17][18][19][20][21][22][23] Nowadays, it still remains a challenge for preparing more complicated microgels with controllable shapes and built-in functionalities for novel applications, which mimic those of some living micro-creatures. Recently, Sarkar and his coworkers modeled the deformation of a viscoelastic drop falling through a Newtonian medium and pointed out that viscoelasticity can make an initially spherical drop deformed into an oblate shape with a dimple at the rear end.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] Non-spherical microgel, such as rod-like, wedge-like, and disk-like microgels, can also be prepared via well-designed microfluidic channels or mask-photopolymerization. [15][16][17][18][19][20][21][22][23] Nowadays, it still remains a challenge for preparing more complicated microgels with controllable shapes and built-in functionalities for novel applications, which mimic those of some living micro-creatures. Recently, Sarkar and his coworkers modeled the deformation of a viscoelastic drop falling through a Newtonian medium and pointed out that viscoelasticity can make an initially spherical drop deformed into an oblate shape with a dimple at the rear end.…”
Section: Introductionmentioning
confidence: 99%
“…To release the chelated Ca 2+ , an acidified carrier fluid is typically applied to decrease the pH through the diffusion of H + from the continuous to the dispersed phase resulting in subsequent internal gelation of the alginate. 29,38,41,[44][45][46] While effective in achieving a slower and more homogeneous gelation process that does not clog microfluidic channels immediately and results in well dispersed microparticles, unfortunately all of these approaches are reliant on a pH drop well below the physiological range and are therefore detrimental to cell viability. A recent study 29 showed that cell viability can somewhat be enhanced if the cell-loaded gels are rinsed from the acidic environment shortly after gelation, however, even after short time scales (~2min), the survival rate of the encapsulated cells showed a decrease to ~80% and to ~0% after 30 min between encapsulation, gelation and resuspension in cell medium.…”
Section: Comparison With Other Gelation Strategiesmentioning
confidence: 99%
“…29,41 Introducing aqueous Ca 2+ directly to the alginate stream in a device will result in immediate gelling and clogging of the channels. Therefore, in addition to having an inlet for Ca 2+ and alginate, an extra inlet is often introduced to the microfluidic geometry whereby sheathing buffer is injected to temporary shield the Ca 2+ stream from the alginate.…”
Section: Comparison With Other Gelation Strategiesmentioning
confidence: 99%
“…Gelation is then triggered by an additional substance ͑e.g., acetic acid͒ diffusing into the droplet from the continuous phase. 10,24,25,28,29 Finally, in coalescence-induced gelation two aqueous droplets, one with the biopolymer and one with the ions, are coalesced to induce cross-linking. [30][31][32] Combined methods are also known.…”
Section: Introductionmentioning
confidence: 99%